Accurate potential energy surfaces for the first two lowest electronic states of the Li (2p) + H2 reaction. Issue 28 (25th April 2018) - Fu, Liwei; Wang, Dequan; Huang, Xuri
Abstract : Accurate diabatic potential energy surfaces for the Li (2p) + H2 → LiH (X) + H reaction are produced. Abstract : The accuracy of three-dimensional adiabatic and diabatic potential energy surfaces is calculated using ab initio methods and is numerically fitted for the two lowest electronic states 1 and 2 2 A′ of the LiH2 system, which are very important for the Li (2p) + H2 reaction. The finite difference method is performed to generate the mixing angles, which are used to educe the diabatic potential from the adiabatic potential. The accurate conical intersection (CI) is studied in this work with three different basis sets. The energy of the conical intersection is slightly lower (nearly 0.12 eV) than that of the perpendicular intermediate on the first excited state. By analyzing the potential energy surfaces in this work we can suggest that the most possible reaction pathway for the title reaction is Li (2p) + H2 → LiH2 (2 2 A′) (C2 v ) → CI → LiH2 (1 2 A′) (C2 v ) → LiH⋯H → LiH (X 1 ∑ g + ) + H. The conical intersection and (2 2 A′) intermediate may play a vital role in the title reaction.